2018
DOI: 10.1002/art.40513
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Baminercept, a Lymphotoxin β Receptor Fusion Protein, in Primary Sjögren's Syndrome

Abstract: In this trial, treatment with baminercept failed to significantly improve glandular and extraglandular disease in patients with primary SS, despite evidence from mechanistic studies showing that it blocks LTβR signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Unexpectedly, 6 months of baminercept treatment failed to improve glandular dysfunction in patients with primary SS. Although not achieving expected treatment efficacy, the studies revealed, to some extent, the therapeutic effect of baminercept in LT/LIGHT-dependent pathways, suggesting that blocking LTβR signaling might be of therapeutic benefit at earlier stages (121). Both treatments resulted in decreased serum CXCL13 levels in patients with RA, but baminercept treatment was unable to diminish the serum levels of BAFF, LIGHT, or IP-10 compared to the placebo group (119,120).…”
Section: Discussionmentioning
confidence: 90%
“…Unexpectedly, 6 months of baminercept treatment failed to improve glandular dysfunction in patients with primary SS. Although not achieving expected treatment efficacy, the studies revealed, to some extent, the therapeutic effect of baminercept in LT/LIGHT-dependent pathways, suggesting that blocking LTβR signaling might be of therapeutic benefit at earlier stages (121). Both treatments resulted in decreased serum CXCL13 levels in patients with RA, but baminercept treatment was unable to diminish the serum levels of BAFF, LIGHT, or IP-10 compared to the placebo group (119,120).…”
Section: Discussionmentioning
confidence: 90%
“…Figure 1 summarises the SLR results. Summary-of-finding tables were generated for RCTs (table 1),10 12–19 prospective cohort studies (table 2)20–37 and case-control studies (table 3). 38–42 For RCTs, the risk of bias (RoB) was assessed using the Cochrane RoB assessment tool (Cochrane Handbook for Systematic Reviews of Interventions V.5.1.0 March 2011 (available from: http://handbook.cochrane.org/)), and for uncontrolled studies, we used the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement checklist.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary results were presented at the 2015 ACR meeting in San Francisco. 47 Primary endpoint was improvement of pilocarpine-stimulated whole salivary flow and was not achieved. However, ESSDAI improved significantly more in the baminercept group than the placebo group.…”
Section: Germinal Centerlike Structures: a Promising Targetmentioning
confidence: 99%